Hubungan antara Anonimitas dengan Cyber Incivility pada Pengguna Media Sosial Usia Dewasa - Khairiyah, Salmaa (Lembaga Yasin AlSys, 2024)
The development of information and communication technology through the internet has facilitated the communication process on various platforms. This convenience gives individuals the freedom to express their opinions. Individuals will express their opinions without having to issue negative sentences such as sarcasm, innuendo, and others. This is what is called cyber incivility. The freedom to express opinions on social media is increasingly prevalent because of anonymity. Anonymity is a condition where other people do not know the true identity of the individual. The purpose of this study was conducted to see the relationship between cyber incivility and anonymity. The subjects in this study amounted to 301 respondents obtained from the cluster random sampling method. Based on the results of the product moment test using SPSS, a significance value of 0.000> 0.05 was obtained, it can be concluded that there is a relationship between anonymity and cyber incivility. Based on the results of the independent sample t-test, a significance value of 0.198 > 0.05 is obtained, it can be concluded that there is no difference in cyber incivility based on working and not working.